The Socio-Epidemiological Environment and the Health of Infants without Having Been Impacted by Maternal HIV Infection - S. N. Shugaeva; E. D. Savilov; A. G. Petrova (Эпидемиология и вакцинопрофилактика)
The results of a cohort study of 177 newborns, from birth until they were 18 months old, are presented. The 87 of those children had lacked impact of maternal HIV infection, and 90 children were not exposed to HIV prenatally. Antisocial factors were observed among the newborns exposed to a prenatal HIV infection which had a negative impact upon them throughout infancy. The social deviance of their family members with a HIV infection was 10.5 times higher than the standard risk of a neonatal abstinence syndrome, 4 times higher than a standard risk of growth retardation during fetal development, and 3.8 times higher than a standard risk of postnatal development disorders. Undiagnosed infants who were exposed to a HIV-infection constitute a medico-social risk group requiring scrupulous and extended medical assistance.